HUBUNGAN STATUS GIZI TERHADAP ACTIVITY of DAILY LIVING (ADL) PASIEN TB PARU DI RSUD ARIFIN ACHMAD PEKANBARU - Atika Ulfa Putri; Siti " Rahmalia; Juniar " Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Total number of patient with tuberculosis is increased every year. One of the problem is nutritional status is not good.  The aim of the research is to identify the correlation between nutritional status and ADL among pulmonary tuberculosis patients in Lung Tuberculosis ward Arifin Achmad Hospital. The research was designed by correlation wtih cross sectional. The total sample are 44 respondents with purposive sampling based on inclusion criteria. The data was collected by measuring body weight and height and observation. IMT to measure nutritional status and Barthel index to observe ADL. The data was analyzed by Kolmogorov-Smirnov test and the result showed that there is correlation between nutritional status and ADL among pulmonary tuberculosis patient with degree p value (0.042) < α (0.05). Based on the results of this research, the  nurses should be monitor the nutritional status to increase ADL among pulmonary tuberculosis patients. Keyword: nutritional status, pulmonary tuberculosis, ADL.